Innovation and Business Development in the Kebumen Tile Center Industry: A Comprehensive Analysis of Competitiveness, Technology Modernization, and Sustainability Strategies - Reza Widhar Pahlevi; Achmad Fauzi; Nurhayanto; Hermenegildus Agus Wibowo; Marita Nurharjanti; Rosyidah Jayanti Vijaya (BHATARA: Jurnal Multidisiplin Ilmu, 2026)
This study aims to examine business innovation and development in the Kebumen roof tile industrial cluster through a comprehensive analysis of competitiveness, technological modernization, and sustainability strategies among micro, small, and medium-sized enterprises (MSMEs). The research employed a qualitative case study approach. Data were collected through in-depth interviews with business owners and managers of the Kebumen roof tile industry cluster, complemented by field observations and documentation to enhance data validity through source triangulation. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings reveal that the competitiveness of the roof tile industry is largely determined by the enterprises' ability to develop product innovation, maintain product quality, expand marketing networks, and strengthen customer relationships. Technological modernization has improved production efficiency; however, its implementation remains constrained by limited financial resources, inadequate human capital, and restricted access to advanced technologies. Sustainable business strategies adopted by MSMEs include product diversification, digital marketing adoption, human resource development, collaboration with government agencies and supporting institutions, and the implementation of environmentally friendly production practices. These findings provide practical implications for policymakers and stakeholders in designing innovation-driven empowerment programs to enhance the long-term competitiveness and sustainability of MSMEs in traditional manufacturing industries.